نظريَّة التَّواصل المفهوم والمصطلح - القضماني, رضوان; العكش, أسامة (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
لقد شهدت العلوم المعرفيَّة ازدهاراً كبيراً نتيجة العمل الجادِّ في شتى حقولها, وقد واكب علم اللِّسانيَّات ذلك الازدهار بما شهده من بحوث مستمرَّة حاولت جاهدة أن تقوِّم مسيرته؛ تجلَّت في علوم الرِّياضيَّات, والفلسفة, والفلك, والاتِّصالات السِّلكيَّة واللاسلكيَّة, فبرز في هذا المجال عالم اللُّغة الرُّوسيّ الشَّهير (رومان ياكبسون) الَّذي تميَّـز بمـا وصل إليه؛ إذ حدَّد جوهر التَّواصل اللِّسانيِّ بأركانه السِّتة, ووظائفه السِّتِّ, ومفهوم الوظيفة المهيمنة, وما لها من مهمَّة في توجيه العمل الأدبيِّ. لذا آثر هذا البحث أن يتناول نظريَّة التَّواصل في المفهوم والمصطلح, ويوضِّح عناصر نظريَّة التَّواصل, ووظائفها, ومهمَّة الوظيفة المهيمنة, وما لها من أهمِّية في مجال البحوث المعرفيَّة حسب فهم (ياكبسون). Epistemology sciences have witnessed great progress as a result of the serious work in its different fields. Similarly, linguistics kept in step with that progress through the continuous researches which tried hard to straighten progress embodied in Math, Philosophy, Astronomy and Wired and Wireless communication sciences. The Russian linguist, Roman Jakobson was distinguished in this field of science. He determined the essence of the linguistic connection: its six foundations, six functions as well as the concept of the dominationg function theory and its role in directing the literary work. This research studies the connection theory in concept and idiom and clarifies the elements of the connection theory as well as its functions and the role of the dominating function theory and its importance in the field of epistemology according to Jakobson’s view.